Financial Inclusion Effect on Core Poverty During The Pandemic Period in East Java - Abdus Salam; Hermanto Hermanto (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Statistika STIS, 2020)
Poverty is increasing globally at this time especially the impact of the Covid-19 pandemic. Meanwhile, the banking sector has a role to play in controlling the growing poverty, one of which is through financial inclusion. In some areas, the financial inclusion index has improved, indicated by the number of people who have switched from traditional savings to financial institution savings and have also reached the infrastructure of conventional commercial banks, but the fact has not yet reached the “usefulness of banking services”. So that financial inclusion is not really felt by the community. This study uses data from the March 2020 National Socio-Economic Survey (Susenas) and Podes 2020 to determine the effect of financial inclusion on core poverty. From the results of the logit regression estimation, it was found that financial inclusion had a strong effect on the status of core poverty in households when the COVID-19 pandemic hit in East Java (2020). Ownership of bank accounts has a strong and negative effect on poverty. The farther the distance to banking facilities, the greater the chance of experiencing poverty. Access to formal credit has the opportunity to move away from poverty. Education remains a key variable if you want to be free from poverty. The added value of farming households is still not optimal in increasing welfare, because they still have the opportunity to experience poverty. Access to information technology in households can increase opportunities to be more prosperous. From these results, the government should seek to increase public participation in having a bank account through banking literacy, through formal education, adding infrastructure for financial institutions evenly to villages, expanding access to formal credit services, and adding cellular/internet network infrastructure up to suburbs (rural/remote areas).